A Country Once Great? Asylum Seekers, Historical Imagination, and the Moral Privilege of Whiteness. Issue 4 (1st October 2016) - Ricatti, Francesco
ABSTRACT: The current public debate on asylum seekers arriving to Australia by boat is profoundly emotional and divisive. Its emotional nature must not only be considered in the present context but also understood from a historical perspective. This article argues that often the asylum seeker debate has been structured as an emotional dispute about the morality of the Australian nation; and that one of the main functions of such a dispute is to reinstate the moral privilege of whiteness. This has weakened the ability of human rights activists to advocate for the ending of current policies, and has instead reinforced an insular, exclusionary and rhetorical understanding of Australian history. On both sides of the debate, historical amnesia and the rhetorical celebration of the past have at times worked hand in hand with allegedly pragmatic approaches to the "boat people" crisis. Yet it is only in addressing the repressed and haunting memories of the past that Australians might find critical and creative antidotes to the merciless dictates of pragmatic politics.